Techniques for Maximizing the Performance of Molecular Pathology Testing: Responsibilities of All Pathologists - Evren UZUN; Sülen SARIOĞLU (Federation of Turkish Pathology Societies, 2018)
Molecular pathological analysis has an expanding role in patient diagnosis and management. The performance of these techniques relies on excellent laboratory procedures. However, the crucial step is obtaining the best samples for molecular analysis. Archiving and selection of these are the responsibilities of all pathologists even if they are not working at a center with molecular pathological facilities. This review focuses on the features of different types of materials for molecular pathological analysis. Many steps that might affect the results, including communication between the pathologist and the oncology team, features of different types of materials (cytological, tissue blocks, biopsy, circulating tumor cells (CTCs) and cell-free circulating nucleic acids), effects of tissue processing, methods for selecting the best material, and tissue saving and tumor enrichment methods are discussed. The procedures for referral to a center for molecular pathological analysis are also mentioned. Awareness of the importance of the cytopathological and histopathological material of the patients for future molecular pathological analysis by pathologists is of the utmost importance.